EFEKTIVITAS BUBU LIPAT PAYUNG UNTUK MENANGKAP IKAN SELUANG (Rasbora argyotaenia) DI SUNGAI MENTENANG KECAMATAN JANGKAT KABUPATEN MERANGIN PROVINSI JAMBI - Dicky Kurniadi; Syafrialdi Syafrialdi; Muhammad Natsir Kholis (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2022)
Bubu is a passive fishing gear designed to catch various types of fish, crustaceans, mollusks and others, with various shapes and made of various materials. One type is a folding umbrella trap which is now widely operated in the waters of Jangkat, Jambi. The main catch target is seluang fish. The purpose of the research was to determine the effect of the number of entrances (funnels) on the average catch and to determine the effectiveness of umbrella traps. The research method is experimental fishing. The results showed that there was a difference in the average catches of funnel 6 and funnel 8 traps based on the results of the calculation of T hit (2.85) T tab (2.18). Umbrella traps of funnel 6 and funnel 8 are not effective in catching seluang fish (Rasbora argyotaenia) because E 1. However, folding umbrella traps can be said to be effective in catching seluang fish when viewed from the number of catches per species, not based on target and non-target fish.